RESEARCH IN AID OF TEACHER TRAINING AS A CENTRAL COMPONENT IN THE PROCESS OF PROFESSIONAL LEARNING - Teresa Sarmento; Rosenilde Paniago (Editora da Universidade de Santa Cruz do Sul, 2016)
The Bologna process introduced changes in teacher's training process in Portugal, forcing a reorganization of its syllabi. The training must occur in two study cycles: undergraduate and master. Master graduation integrates the research component, understood as 'research service practices'. In this paper, after a documentary contextualization, we analyzed narratives of eight teachers, about their representations of the influence of research in decision-making in the pedagogical routine as well as the relevance of this training component to the increase of awareness in the process of professional learning. The initial findings of this study point out the progressive awareness of Masters students of how research helps to support professional learning and to promote their commitment to a continuous search path in a permanent professionalization process.